2021
DOI: 10.18203/2394-6040.ijcmph20210206
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer and breast self-examination awareness among undergraduate students of the University of Bamenda, Cameroon

Abstract: Background: Breast self-examination (BSE) is an individual check-up to identify any health problem in the breast, especially breast cancer. However, though the university is the place of high education, the level of the student knowledge about breast cancer and BSE remains not quite known. This study aimed to identify awareness on breast cancer and BSE among the student population of The University of Bamenda, Cameroon.Methods: A well designed descriptive study was carried out using a structured questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…14 In this study, when asked about the age at which BSE should be performed, only 24 (4%) participants responded correctly as more than 19 years of age, while in comparison to a study done by Choumessi et al only 7.06% of the of them indicated that BSE should be done as from 20 years. 15 Hence health education has to be done to improve the knowledge of the studied population about BSE.…”
Section: Discussionmentioning
confidence: 99%
“…14 In this study, when asked about the age at which BSE should be performed, only 24 (4%) participants responded correctly as more than 19 years of age, while in comparison to a study done by Choumessi et al only 7.06% of the of them indicated that BSE should be done as from 20 years. 15 Hence health education has to be done to improve the knowledge of the studied population about BSE.…”
Section: Discussionmentioning
confidence: 99%